Commercialising of innovative research product in the Malaysian public university: challenges and ways for improvement - Ismail, Norain; Mohamed, Khadijah (Academic Journals Inc., 2016)
Commercialization of an innovative research product has been perceived as a platform to increase the wealth for a country including Malaysia.Although many efforts have been emphasized to encourage for commercialization activities, the rate of success is still less encouraging.Thus, the purpose of this study is to examine the challenges faced by academic researchers in commercializing their innovative research products and to suggest ways for improvement for commercialization activities particularly in the university.Interviews were conducted with five academic researchers who have successfully commercialized their innovative research products. This study identified that there are main challenges with respect to intellectual property protection and commercialization policy, producing innovative research products and gaps between academics and industry collaborators.The most challenging factor is the intellectual property protection and commercialization policy.